2019
DOI: 10.1002/ptr.6574
|View full text |Cite
|
Sign up to set email alerts
|

Tart cherry (Prunus cerasus L.) fractions inhibit biofilm formation and adherence properties of oral pathogens and enhance oral epithelial barrier function

Abstract: Dental caries, candidiasis, and periodontal disease are the most common oral infections affecting a wide range of the population worldwide. The present study investigated the effects of two tart cherry (Prunus cerasus L.) fractions on important oral pathogens, including Candida albicans, Streptococcus mutans, and Fusobacterium nucleatum, as well as on the barrier function of oral epithelial cells. Procyanidins and quercetin and its derivatives were the most important constituents found in the tart cherry fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
(43 reference statements)
2
16
0
Order By: Relevance
“…Non-dialyzable material was freeze-dried and stored at 4˚C in the dark. The phenolic composition of the tart cherry extract determined by chromatographic and mass spectrometry analyses has been reported previously [23]. Quercetin and its derivatives (rutinoside, glucoside) as well as procyanidins are the main constituents of the extract.…”
Section: Preparation Of the Tart Cherry Phenolic Extractmentioning
confidence: 73%
See 2 more Smart Citations
“…Non-dialyzable material was freeze-dried and stored at 4˚C in the dark. The phenolic composition of the tart cherry extract determined by chromatographic and mass spectrometry analyses has been reported previously [23]. Quercetin and its derivatives (rutinoside, glucoside) as well as procyanidins are the main constituents of the extract.…”
Section: Preparation Of the Tart Cherry Phenolic Extractmentioning
confidence: 73%
“…were immunostained with either occludin antibody-Alexa Fluor 488 conjugate or ZO-1 antibody-Alexa Fluor 594 conjugate (Thermo Fisher Scientific, Waltham, MA, USA), as described previously [23]. An Olympus FSX100 fluorescence microscope and FSX-BSW imaging software (Olympus, Tokyo, Japan) were used to observe the immunostaining.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The oral cavity is a complex bacterial ecosystem composed of multiple microorganisms that intimately coexist [26][27][28][29][30]. Bio lms are one way they coexist [31,32], and they develop thanks to multiple mechanisms associated with protein expression [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have showed that cherry fruit or juice consumption plays an important role in inflammatory diseases [54][55][56] by preventing or reducing inflammation related to muscle damage from intense strength exercise and also by accelerating recovery from strenuous physical activity. Ben Lagha et al [57] reported that the tart cherry fractions and their bioactive constituents have antiplaque action due to their ability to inhibit the adherence properties of oral pathogens and increase the epithelial barrier function. Moreover, a recent study has confirmed the importance of cherry fruit in ATS risk factors prevention due to the effect of its polyphenols to reduce inflammation and endothelial dysfunction [58].…”
Section: Polyphenols and Sweet Cherry (Prunus Avium L)mentioning
confidence: 99%